Polip Antrokoanal Angiomatosa pada Remaja 17 Tahun di RSUD Pasar Rebo - Agisni Kartika Rachmadini; Indah Trisnawaty; Hastuti Rahmi (Lembaga Pengembangan Kinerja Dosen, 2026)
Antrochoanal polyps are solitary lesions originating from the maxillary sinus and extending into the nasal cavity and nasopharynx. The angiomatous variant is rare and is characteristically associated with recurrent epistaxis due to prominent vascular proliferation within the polyp. We report a case of a 17-year-old male who presented with recurrent epistaxis for four months, accompanied by nasal obstruction and frequent sneezing. Nasoendoscopic examination revealed a friable mass in the left middle meatus with a tendency to bleed on contact. Computed tomography (CT) scan demonstrated a hyperdense mass measuring approximately 1.5 × 2.2 × 2.7 cm occupying the left nasal cavity and extending into the left maxillary sinus, without evidence of bony destruction. Histopathological examination confirmed the diagnosis of an angiomatous antrochoanal polyp. The patient initially received conservative medical management aimed at maintaining nasal cavity hygiene, including 0.9% normal saline irrigation, loratadine 10 mg, and cefixime 200 mg, along with education regarding proper nasal hygiene. Definitive treatment was subsequently performed with left-sided Functional Endoscopic Sinus Surgery (FESS). Intraoperative findings a reddish polipoid mass that bled easily was observed, and postoperatively the nasal cavity appeared patent with no residual mass. This case is consistent with the literature, which states that antrochoanal polyps are more common in children and adolescents, are typically unilateral, and that definitive treatment is endoscopic surgery with a good prognosis, although the risk of recurrence remains.